ReSurveyChaMon: A dataset of resurvey vegetation plots of the Argentine drylands - Giorgis, Melisa Adriana (2025)
The ReSurveyChaMon dataset provides a unique set of resurveyed vegetation plots spanning the sharp ecological transition between the Arid Chaco woodlands and the Monte steppe in central-western Argentina. The original plots were established in 1990 along a 300-km east-west transect covering a strong precipitation gradient, from xerophytic woodlands to desert shrublands, and were resurveyed in 2025 using the same protocol and plot size. In total, 104 vegetation plots are included in the dataset (52 original and 52 resurveyed). The dataset contains 164 vascular plant taxa from 113 genera and 41 families, with Poaceae, Fabaceae, and Cactaceae being the richest families. Species were assigned to life forms and chorotypes, and their native and endemic status (4 non-native and 39 endemic taxa) was also documented. All plots have been georeferenced, allowing integration with remote sensing and environmental data for future temporal and spatial analyses. ReSurveyChaMon offers an unprecedented opportunity to explore fine-scale vegetation dynamics across one of South America’s least studied dryland regions and provides a valuable baseline for biodiversity monitoring, conservation planning, and assessment of climate- and land-use-driven changes in arid and semi-arid ecosystems.